Komunikasi Persuasif Dosen dalam Memberikan Motiviasi untuk Mahasiswa Kebidanan: Lecturer Persuasive Communication in Providing Motivation for Midwifery Students - Elsaid, Dea Audia; Alza, Nurfaizah; Suherli; Jamal, Muh Nurqadri; Desiana, Istiqamah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Persuasive communication is a process and strategy in communication to convey the lecturer's message and motivation to students to implement positive things that a student should have. Method This study uses a qualitative method. The data collection technique is by interviewing and then getting the results by describing them in the form of words. Result The students gave almost the same responses. Assumes that the Midwifery Study Program Lecturers have carried out positive persuasive communication in providing motivation to students. This always happens before or after class starts. Conclusion In this series of communications there is positive motivation and the lecturer applies psychodynamic strategies to touch the psychological aspects of students.